Deputy Scarlett - Boyle, Doe.; Langford, Alton (Norwalk, Conn. : Soundprints, 1992)
A homeless fox arrives in the Deep Green Wood in time to rescue Ranger Rick and end the squabbling over who will be his assistant.
"From an original article which appeared in Ranger Rick magazine."
Keywords: Leadership -- Fiction; Raccoons -- Fiction; Foxes -- Fiction; Animals -- Fiction